2021
DOI: 10.3390/biomedicines9111697
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease (NAFLD) and Potential Links to Depression, Anxiety, and Chronic Stress

Abstract: Non-alcoholic fatty liver disease (NAFLD) constitutes the most common liver disease worldwide, and is frequently linked to the metabolic syndrome. The latter represents a clustering of related cardio-metabolic components, which are often observed in patients with NAFLD and increase the risk of cardiovascular disease. Furthermore, growing evidence suggests a positive association between metabolic syndrome and certain mental health problems (e.g., depression, anxiety, and chronic stress). Given the strong overla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 103 publications
1
40
0
5
Order By: Relevance
“…Currently, increasing evidence suggests a strong association between NAFLD/NASH and psychological disorders, such as depression [ 30 , 31 ]. We found out that patients with NAFLD had significantly higher scores on HADS-D, compared with the controls (4 [2–6] vs. 2 [0–4], respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, increasing evidence suggests a strong association between NAFLD/NASH and psychological disorders, such as depression [ 30 , 31 ]. We found out that patients with NAFLD had significantly higher scores on HADS-D, compared with the controls (4 [2–6] vs. 2 [0–4], respectively).…”
Section: Discussionmentioning
confidence: 99%
“…One study showed negative correlation of DNAm of cg03341655 in the subcutaneous adipose tissue in response to high saturated fatty acids diet [ 39 ]. In fact, both, PD and MDD, as well as chronic stress are related to higher risk of metabolic syndromes and cardiovascular morbidity as has been shown in multiple studies [ 40 42 ]. Further EWAS have reported DNAm changes at different CpG-sites in GFOD2 in relation to childhood abuse [ 43 ], maternal alcohol consumption and offspring cord blood methylation [ 44 ] and all-cause mortality in monozygotic twins [ 45 ].…”
Section: Discussionmentioning
confidence: 97%
“…Some researchers have suggested the influence of chronic stress on the development of liver damage in people with obesity. According to this theory, as in type 2 diabetes and cardiovascular disease, stress involves both behavioral and biological responses, which activate the hypothalamic -pituitaryadrenal axis, resulting in elevated levels of cortisol and pro-inflammatory biomarkers that could be involved in the development of MAFLD (24,25). Also, pro-inflammatory pathways, immune dysregulation, and systemic or multi-organ inflammation are considered to mediate pathophysiological interaction between certain mental health disorders (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…According to this theory, as in type 2 diabetes and cardiovascular disease, stress involves both behavioral and biological responses, which activate the hypothalamic -pituitaryadrenal axis, resulting in elevated levels of cortisol and pro-inflammatory biomarkers that could be involved in the development of MAFLD (24,25). Also, pro-inflammatory pathways, immune dysregulation, and systemic or multi-organ inflammation are considered to mediate pathophysiological interaction between certain mental health disorders (25,26). Finally, there are also established relationships between obesity and mental health that may be connected to changes in gut microbiota, resulting in such comorbidity.…”
Section: Discussionmentioning
confidence: 99%